Possibilities of Modern Imaging Methods in Epibulbar Lesions Diagnostics - T. N. Kiseleva; A. N. Bedretdinov; A. L. Batalova; N. I. Ovechkin (Oftalʹmologiâ, 2025)
Aim of the study: to study the informativeness of new modes of standardized A-echography in the diagnosis of retinal detachment, vitreous adhesions, and retinoschisis.Patients and methods. The study included 180 patients (180 eyes) with vitreoretinal pathology aged 40 to 78 years (mean age 62 ± 6.2 years): 70 patients (70 eyes) with local retinal detachment (RD), 70 patients (70 eyes) with vitreous adhesions, and 40 patients (40 eyes) with retinoschisis (RS). All patients underwent a comprehensive ultrasound examination, including B-echography and standardized A-echography in the modes of quantitative evaluation of echo signals Retina I (evaluation of the number of echo signal microoscillations) and Retina QII (evaluation of the difference in reflectivity (DR) in comparison with the sclera).Results. According to B-echography, RD was diagnosed in 66 patients (94.29 %), vitreous adhesions — in 63 cases (90 %), retinoschisis — in 36 patients (90 %), in 15 patients (25 %) the assessment of the detected pathological intraocular abnormalities was complicated due to the similarity of the echographic image. According to standardized A-echography, RD was recorded in 65 cases (92.86 %). The results of the echo signal microoscillations assessment in the Retina A1 mode corresponded to “R++” and “R+++”, the DR in the Retina QII mode corresponded to 10.56 ± 3.18 dB. Vitreous adhesions were recorded in 63 cases (90 %). In the Retina A1 mode, the indicators corresponded to “M++” and “M+++”, the DR was 25.45 ± 5.56 dB (Retina QII mode). In patients with RD in the Retina A1 mode, the values  corresponded to “R++” and “R+++” in 32 patients (80 %) and “M++” in 8 patients (20 %), the DR in the Retina QII mode was 21.44 ± 6.78 dB. When comparing the DR values  (Retina QII mode) in the groups with RD and vitreous adhesions, the difference was statistically significant (p < 0.01). The difference in the DR values  in the RD group was significant when compared with patients with vitreous adhesions (p < 0.05) and insignificant when compared with patients with RD (p > 0.05).Conclusion. New modes of standardized A-echography in combination with traditional B-echography makes it possible to significantly increase the informative value of ultrasound diagnostics of RD, vitreous adhesions and retinoschisis.